Optimizing and coordinating the location of raw material suitable for cement manufacturing in Wasit Governorate, Iraq - Shadhar Alaa Kharbat; Mahmood Buroog Basheer; Abboud Abdulhassan Aqeel; Mahjoob Ahmed Mohammed Raoof; Shamkhi Mohammed S. (Open Engineering, 2023)
The cement industry is considered one of the strategic industries, because it is directly related to construction work and cement is used as a hydraulic binder. However, it is a simple industry compared to major industries and depends on the availability of the necessary raw materials. This study focuses on optimizing and coordinating the location of raw materials needed for the cement manufacturing in Wasit Governorate in Iraq. Field works include detailed reconnaissance, topographic work, and description and sampling of 24 lithological sections that represent the carbonate deposits, which crop out in the area. The investigated area has the following specifications: The weighted averages of chemical components in the industrial bed are as follows: CaO = 47.83%, MgO = 1.12%, SiO2 = 7.28%, SO3 = 0.34%, Fe2O3 = 1.85%, Al2O3 = 1.85%, L.O.I = 39.26%, Na2O = 0.29%, and K2O = 0.38%. The average thickness of the investigated raw materials is 15.68 m. The average bulk density of the investigated raw materials is 2.32 g/cm3. The compressive strength of the investigated raw materials ranges from 6.182 to 55.21 MN/m2. The positive area is 922,552 m2. The volume of the industrial bed is 14,466,242 m3. The economic reserve of the industrial bed is 33,561,682 tons.